PENGARUH PELAKSANAAN SUPERVISI PENDIDIKAN OLEH KEPALA SEKOLAH TERHADAP KINERJA GURU (STUDI KASUS: GURU SDN 12 KOTO TINGGI, KEC. BASO, KAB AGAM 2022) - Rena Elia; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The importance of paying attention to teacher supervision in the world of education in order to contribute to school principals in carrying out their academic supervision optimally and providing knowledge for teachers in motivating themselves to improve their performance. This study aims to determine how much influence the implementation of educational supervision is carried out on elementary school teachers in Baso District. The research method uses a quantitative approach, with a population of all primary school teachers in Baso District in 2022 as many as 52 people. The sample used in the study was the entire population of 52 people, the instrument used was a Likert scale questionnaire. Data analysis used the help of the IBM SPSS 20 software program. The results of the research implementation of teacher supervision in Baso District, Agam Regency had a positive and significant effect with a significance value of 0.002, this is smaller than 0.05 and the value of T Count>T Table or 2.995> 2.00665. with a large contribution of influence given the implementation of teacher supervision in Baso District on teacher performance by 18.3%.